Assessment of right ventricular function and relation to mortality after acute pulmonary embolism: A speckle tracking echocardiography-based study - (:unkn) unknown (WILEY, 2019)
Purpose Right ventricular (RV) dysfunction is a common condition that is related to increased adverse outcomes in patients with acute pulmonary embolism (APE). Our aim was to assess timing and magnitude of regional RV function using speckle tracking echocardiography (STE) and to evaluate their relationship to long-term mortality in patients after APE. Methods In total, 147 patients were enrolled at the onset of an APE episode and followed for 12 +/- 1.1 months. For all patients, the clinical, laboratory, and echocardiography examinations were performed at the diagnosis of APE and at the end of the 1-year follow-up. Results Of the 147 patients, 44 (29.9%) died during the 1-year follow-up after APE. The patients who died had lower RV free wall peak longitudinal systolic strains (PLSS) and left ventricular (LV) PLSS and higher RV peak systolic strain dispersion (PSSD) index which means the electromechanical dispersion when compared with the survivors. The difference in time to PLSS between the RV free wall and LV lateral wall (RVF-LVL) which means the electromechanical delay was longer in patients who died than in those who survived during follow-up, and this difference was an independent predictor of mortality at 1 year of follow-up after APE, with 86.4% sensitivity and 81.7% specificity. At the end of 1-year follow-up, the RV free wall PLSS and the LV global PLSS increased, whereas the RV PSSD index and the difference in time to PLSS between the RVF and LVL decreased. Conclusions Acute pulmonary embolism was associated with RV dysfunction and RV electromechanical delay and dispersion. These parameters improved at the end of 1-year follow-up. The electromechanical delay index might be a useful predictor of mortality in patients after APE.
Keywords: electromechanical delay; pulmonary embolism; right ventricle; speckle tracking echocardiography; EUROPEAN ASSOCIATION; AMERICAN SOCIETY; RIGHT HEART; STRAIN; DYSSYNCHRONY; GUIDELINES; CARDIOLOGY; ADULTS